ANALISIS KINERJA PEGAWAI DENGAN MENGGUNAKAN BERBAGAI ALTERNATIF METODE ANALISIS - Budiwinarto, Kim (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2014)
This research aims to assess employee performance analysis using two alternative solution methods of analysis due to multicollinearity problem on on the linear regression analysis. This research review of sight analysis method in statistical. The data used in this study is the result of a survey employee performance at the Badan Pelayanan Perizinan Terpadu Office of Kabupaten Karanganyar in February 2014. Linear regression analysis of the results, it turns out there is a problem of multicollinearity. To that end, in this study provided two alternative solutions. The first solution is to pass a single independent variable i.e. job satisfaction variables. While the second solution is the path analysis that maintains all the variables are independent. Keywords: model, linear regression analysis, path analysis, multicollinearity, employee performance, work motivation, job satisfaction, work stress.